Analisis Penerapan Bauran Promosi Sebagai Komunikasi Pemasaran Pt Bhineka Rahsa Nusantara Dalam Mempromosikan Produk Rahsa Nusantara Di Kota Bandung - Furqon, Al-fitra; Wijaksono, Dimas Satrio (eProceedings of Management, 2024)
The Covid-19 outbreak has changed many people's lifestyles, including healthy consumption patterns. Although manyindustries have been harmed by the pandemic, the herbal industry has actually increased and has bright prospects forthe future. This study aims to describe the application of the promotion mix by PT Bhineka Rahsa Nusantara inmarketing Rahsa Nusantara products in Bandung City. Using descriptive qualitative research methods with aninterpretive paradigm, as well as Kotler and Armstrong's Promotion Mix theory (2008), data was collected throughinterviews, observations, and documentation. The results showed that PT Bhineka Rahsa Nusantara has implementedthe five elements of the promotion mix well. In the Advertising indicator, they use online and offline channels, such asads on social media and flyers at certain events. In Sales Promotion, they offer discounts, vouchers, cashback, freebies,and mini size products. For Public Relations, they hold webinars on health issues and collaborate with relevant mediaand communities. For Personal Selling, they participated in several events to sell products directly. Finally, for DirectMarketing, they send email and WhatsApp blasts to notify consumers of promotions. Keywords-herbal drinks, promotion mix, Rahsa Nusantara.